High PRDM16 expression identifies a prognostic subgroup of pediatric acute myeloid leukaemia correlated to FLT3‐ITD, KMT2A‐PTD, and NUP98‐NSD1: the results of the Japanese Paediatric Leukaemia/Lymphoma Study Group AML‐05 trial. (18th December 2015) - Shiba, Norio; Ohki, Kentaro; Kobayashi, Tohru; Hara, Yusuke; Yamato, Genki; Tanoshima, Reo; Ichikawa, Hitoshi; Tomizawa, Daisuke; Park, Myoung‐ja; Shimada, Akira; Sotomatsu, Manabu; Arakawa, Hirokazu; et al.
Summary: Recent reports described the NUP98‐NSD1 fusion as an adverse prognostic marker for acute myeloid leukaemia (AML) and PRDM16 (also known as MEL1 ) as the representative overexpressed gene in patients harbouring NUP98‐NSD1 fusion. PRDM16 gene expression levels were measured via real‐time polymerase chain reaction in 369 paediatric patients with de novo AML, of whom 84 (23%) exhibited PRDM16 overexpression ( PRDM16 / ABL1 ratio≥ 0·010). The frequencies of patients with high or low PRDM16 expression differed widely with respect to each genetic alteration, as follows: t(8;21), 4% vs. 96%, P < 0·001; inv(16), 0% vs. 100%, P < 0·001; KMT2A (also termed MLL )‐ partial tandem duplication, 100% vs. 0%, P < 0·001; NUP98 ‐ NSD1, 100% vs. 0%, P < 0·001. The overall survival (OS) and event‐free survival (EFS) among PRDM16‐ overexpressing patients were significantly worse than in patients with low PRDM16 expression (3‐year OS: 51% vs. 81%, P < 0·001, 3‐year EFS: 32% vs. 64%, P < 0·001) irrespective of other cytogenetic alterations except for NPM1 . PRDM16 gene expression was particularly useful for stratifying FLT3 ‐internal tandem duplication‐positive AML patients (3‐year OS: high = 30% vs. low = 70%, P < 0·001). PRDM16 overexpression was highly recurrent in de novo paediatric AML patients with high/intermediate‐risk cytogenetic profiles and was independently associated with an adverse outcome.